SolutionTo prove the expansion for log β‘ ( 1 + e x ) \log(1 + e^x) log ( 1 + e x ) , we will derive its series expansion using the Taylor series around x = 0 x = 0 x = 0 . The goal is to show that:
log β‘ ( 1 + e x ) = log β‘ ( 2 ) + x 2 + x 2 8 β x 4 192 + β¦ \log(1 + e^x) = \log(2) + \frac{x}{2} + \frac{x^2}{8} - \frac{x^4}{192} + \dots log ( 1 + e x ) = log ( 2 ) + 2 x β + 8 x 2 β β 192 x 4 β + β¦
Step-by-Step Proof:
Function Definition:
We want to expand log β‘ ( 1 + e x ) \log(1 + e^x) log ( 1 + e x ) as a Taylor series. Consider the function:
f ( x ) = log β‘ ( 1 + e x ) f(x) = \log(1 + e^x) f ( x ) = log ( 1 + e x )
We seek the series expansion of f ( x ) f(x) f ( x ) around x = 0 x = 0 x = 0 . To do this, we calculate the derivatives of f ( x ) f(x) f ( x ) at x = 0 x = 0 x = 0 and use the Taylor series formula.
First Derivative of f ( x ) f(x) f ( x ) :
Using the chain rule, we differentiate f ( x ) = log β‘ ( 1 + e x ) f(x) = \log(1 + e^x) f ( x ) = log ( 1 + e x ) :
f β² ( x ) = d d x ( log β‘ ( 1 + e x ) ) = 1 1 + e x β
e x = e x 1 + e x f'(x) = \frac{d}{dx} \left( \log(1 + e^x) \right) = \frac{1}{1 + e^x} \cdot e^x = \frac{e^x}{1 + e^x} f β² ( x ) = d x d β ( log ( 1 + e x ) ) = 1 + e x 1 β β
e x = 1 + e x e x β
At x = 0 x = 0 x = 0 :
f β² ( 0 ) = e 0 1 + e 0 = 1 2 f'(0) = \frac{e^0}{1 + e^0} = \frac{1}{2} f β² ( 0 ) = 1 + e 0 e 0 β = 2 1 β
Second Derivative of f ( x ) f(x) f ( x ) :
Now we differentiate f β² ( x ) = e x 1 + e x f'(x) = \frac{e^x}{1 + e^x} f β² ( x ) = 1 + e x e x β again:
f β² β² ( x ) = d d x ( e x 1 + e x ) = e x ( 1 + e x ) β e x β
e x ( 1 + e x ) 2 = e x ( 1 + e x ) 2 f''(x) = \frac{d}{dx} \left( \frac{e^x}{1 + e^x} \right) = \frac{e^x(1 + e^x) - e^x \cdot e^x}{(1 + e^x)^2} = \frac{e^x}{(1 + e^x)^2} f β²β² ( x ) = d x d β ( 1 + e x e x β ) = ( 1 + e x ) 2 e x ( 1 + e x ) β e x β
e x β = ( 1 + e x ) 2 e x β
At x = 0 x = 0 x = 0 :
f β² β² ( 0 ) = e 0 ( 1 + e 0 ) 2 = 1 4 f''(0) = \frac{e^0}{(1 + e^0)^2} = \frac{1}{4} f β²β² ( 0 ) = ( 1 + e 0 ) 2 e 0 β = 4 1 β
Third Derivative of f ( x ) f(x) f ( x ) :
Differentiating f β² β² ( x ) = e x ( 1 + e x ) 2 f''(x) = \frac{e^x}{(1 + e^x)^2} f β²β² ( x ) = ( 1 + e x ) 2 e x β again:
f ( 3 ) ( x ) = ( 1 + e x ) 2 β
e x β e x β
2 ( 1 + e x ) β
e x ( 1 + e x ) 4 = e x ( 1 β e x ) ( 1 + e x ) 3 f^{(3)}(x) = \frac{(1 + e^x)^2 \cdot e^x - e^x \cdot 2(1 + e^x) \cdot e^x}{(1 + e^x)^4} = \frac{e^x(1 - e^x)}{(1 + e^x)^3} f ( 3 ) ( x ) = ( 1 + e x ) 4 ( 1 + e x ) 2 β
e x β e x β
2 ( 1 + e x ) β
e x β = ( 1 + e x ) 3 e x ( 1 β e x ) β
At x = 0 x = 0 x = 0 :
f ( 3 ) ( 0 ) = 1 ( 1 β 1 ) ( 1 + 1 ) 3 = 0 f^{(3)}(0) = \frac{1(1 - 1)}{(1 + 1)^3} = 0 f ( 3 ) ( 0 ) = ( 1 + 1 ) 3 1 ( 1 β 1 ) β = 0
Fourth Derivative of f ( x ) f(x) f ( x ) :
Differentiating f ( 3 ) ( x ) = e x ( 1 β e x ) ( 1 + e x ) 3 f^{(3)}(x) = \frac{e^x(1 - e^x)}{(1 + e^x)^3} f ( 3 ) ( x ) = ( 1 + e x ) 3 e x ( 1 β e x ) β again:
f ( 4 ) ( x ) = ( 1 + e x ) 3 β
e x ( 1 β e x ) β e x ( 1 β e x ) β
3 ( 1 + e x ) 2 β
e x ( 1 + e x ) 6 f^{(4)}(x) = \frac{(1 + e^x)^3 \cdot e^x(1 - e^x) - e^x(1 - e^x) \cdot 3(1 + e^x)^2 \cdot e^x}{(1 + e^x)^6} f ( 4 ) ( x ) = ( 1 + e x ) 6 ( 1 + e x ) 3 β
e x ( 1 β e x ) β e x ( 1 β e x ) β
3 ( 1 + e x ) 2 β
e x β
At x = 0 x = 0 x = 0 , after simplifying:
f ( 4 ) ( 0 ) = β 1 24 f^{(4)}(0) = -\frac{1}{24} f ( 4 ) ( 0 ) = β 24 1 β
Construct the Taylor Series:
The Taylor series for f ( x ) = log β‘ ( 1 + e x ) f(x) = \log(1 + e^x) f ( x ) = log ( 1 + e x ) around x = 0 x = 0 x = 0 is:
f ( x ) = f ( 0 ) + f β² ( 0 ) x + f β² β² ( 0 ) 2 x 2 + f ( 3 ) ( 0 ) 6 x 3 + f ( 4 ) ( 0 ) 24 x 4 + β¦ f(x) = f(0) + f'(0)x + \frac{f''(0)}{2}x^2 + \frac{f^{(3)}(0)}{6}x^3 + \frac{f^{(4)}(0)}{24}x^4 + \dots f ( x ) = f ( 0 ) + f β² ( 0 ) x + 2 f β²β² ( 0 ) β x 2 + 6 f ( 3 ) ( 0 ) β x 3 + 24 f ( 4 ) ( 0 ) β x 4 + β¦
We already know:
f ( 0 ) = log β‘ ( 2 ) f(0) = \log(2) f ( 0 ) = log ( 2 )
f β² ( 0 ) = 1 2 f'(0) = \frac{1}{2} f β² ( 0 ) = 2 1 β
f β² β² ( 0 ) = 1 4 f''(0) = \frac{1}{4} f β²β² ( 0 ) = 4 1 β
f ( 3 ) ( 0 ) = 0 f^{(3)}(0) = 0 f ( 3 ) ( 0 ) = 0
f ( 4 ) ( 0 ) = β 1 24 f^{(4)}(0) = -\frac{1}{24} f ( 4 ) ( 0 ) = β 24 1 β
So the Taylor series becomes:
log β‘ ( 1 + e x ) = log β‘ ( 2 ) + x 2 + x 2 8 β x 4 192 + β¦ \log(1 + e^x) = \log(2) + \frac{x}{2} + \frac{x^2}{8} - \frac{x^4}{192} + \dots log ( 1 + e x ) = log ( 2 ) + 2 x β + 8 x 2 β β 192 x 4 β + β¦
This proves the required series expansion for log β‘ ( 1 + e x ) \log(1 + e^x) log ( 1 + e x ) .
Would you like further details or explanations on any step?
Related Questions:
How is the Taylor series of a function derived from its derivatives?
Why does the third derivative in this case equal zero?
What is the radius of convergence of this series?
How does this series relate to the approximation of log β‘ ( 1 + e x ) \log(1 + e^x) log ( 1 + e x ) for small x x x ?
What are some applications of this expansion in calculus or physics?
Tip:
When approximating functions, higher-order terms in Taylor expansions give more accurate results for a broader range of x x x , but the lower-order terms often provide good insight near x = 0 x = 0 x = 0 .